(untitled) (Research, Society and Development, 2020)
This study presents the first survey of fossil mammal specimens housed at the collections of the Federal University of Goiás. Here, we describe a set of associated femur and vertebrae fragments, one fragment of tibia, and two left and right maxillary fragments, identified as Eremotherium. Despite its fragmentary condition, the size and morphological aspect of the materials show diagnostic characteristics that suggest their relationship with Eremotherium. These new specimens described here contribute to the paleontology of the Goiás State, which may provide future research investments in collections not yet known, which may increase the knowledge on Pleistocene mammals of Central Brazil.